Population of the Nagorno-Karabakh Autonomous Oblast According to the All-Union Census of 1959 - Hovhannisyan, Gayane (History and Culture, 2022)
The purpose of the article is to reveal the demographic characteristics of the population of the Nagorno-Karabakh Autonomous Oblast according to All-Union Population Census of 1959. The objectives of the study are to present the size, distribution, ethnic composition, gender composition and age structure of the population of Nagorno-Karabakh according to the census data. The study was conducted on the basis of the results of the Soviet population census, other statistical sources and special literature. Descriptive, statistical and analytical methods have been used and applied. Studying the topic, we have come to the conclusion that the All-Union Census of 1959 showed the consequences of the military-political developments of the previous period on the demographic characteristics of the region. As a result of the Great Patriotic War, the deportation of the Armenian population (1949), the labor recruitment, mass emigration, the population of the autonomous oblast has significantly decreased compared to the pre-war period. The ethnic composition of the autonomous oblast was predominantly Armenian․ In the period between censuses, in contrast to a significant decrease in the number and share of the Armenian, Russian and other ethnic communities of the oblast, there was a noticeable increase in the number and share of the Azerbaijani population. In accordance with the post-war demographic patterns, the female population of the oblast significantly predominated over the male. As for the age structure, a sharp decrease occurred in the age group under 15 years old and especially in the age group of 35-44 years old in comparison to the census of 1939. The 1959 census also showed the process of demographic ageing of the population of Nagorno-Karabakh Autonomous Oblast.